Comparative Study on Temperature Response of Hydropower Development in the Dry‐Hot Valley. (17th July 2021) - Wang, D. C.; Zhang, X.; Huang, Y.; Wang, X.; Zhang, W.; Cao, Z. J.; Xin, Y.; Qu, M.
Abstract: Due to the specific hydrothermal conditions of dry‐hot valleys, temperature changes caused by the development of large‐scale hydropower projects may be more extreme than they are in other regions. In this study, we analyzed these temperature changes at four hydropower stations in both dry‐hot and non‐dry‐hot valleys. Based on the calculated relative temperatures of the downstream river and the areas surrounding the reservoirs, we employed two indices to quantify the influence of the reservoirs on the temperatures of these two regions: the downstream river temperature change and the reservoir effect change intensity. Our results are as follows: (a) In the downstream rivers, the temperature regulation effect was more pronounced in the wet season; in the regions surrounding the reservoirs, the temperature regulation effect was more pronounced in the dry season. (b) The downstream river temperature in both the dry‐hot and wet‐hot valleys exhibited noticeable warming in both the wet and dry seasons, while the cold‐dry valley was characterized by cooling in the dry season and warming in the wet season. With the exception of the Liyuan station (where the influence of the reservoir on the downstream temperatures only extended to a distance of 9 km from the dam) during the dry season, the existence of the hydropower stations affected the temperatures of the entire downstream region. (c) For the areas surrounding the reservoir, the presence of a hydropower station mainly caused the temperatures in the dry‐hot valleys to rise and the temperatures in the non‐dry‐hot valleys to decrease. Plain Language Summary: The temperature difference between reservoir and the downstream river at different distances was calculated to establish the downstream river temperature change index. The temperature difference between reservoir and various locations around reservoir area was calculated to establish the reservoir effect change intensity index. The regulation effect of reservoirs on the downstream river temperature and surrounding reservoir temperature was studied in the dry‐hot and non‐dry‐hot valleys, and their differences were compared. Key Points: The difference of surface temperature affected by reservoirs was compared in dry‐hot and non‐dry‐hot valleys To facilitate comparison of the different downstream river temperature changes, downstream river temperature change index was established The reservoir effect change intensity was established to explore how reservoirs regulate the surface temperature in the surrounding areas